Audit Quality: The Impact of Auditor Competence, Independence, and Professionalism with Evidence Competence as Mediator - Ainun, Sri; Djamil, Nasrullah (MUI Kota Pekanbaru, 2024)
One of the problems that still occur in Indonesia today is the This study aims to determine the effect of competence, independence, and auditor professionalism on audit quality with competence evidence as an intervening variable. The population in this study were auditors who worked at the Public Accounting Firm in Pekanbaru. The number of samples in this study were 77 auditors. The sampling technique used is non-probability sampling, namely purposive sampling. Data collection was carried out by distributing questionnaires. Data analysis used is SEM (Structural Equation Modeling). The results showed that: (1) Auditor competence has no effect on audit quality, (2) Auditor competence has no effect on evidence competence, (3) Indepedence has no effect on audit quality, (4) Indepedence has no effect on evidence competence, (5) professionalism affects audit quality, (6) professionalism affects evidence competence, (7) Evidence competence affects audit quality, (8) Auditor competence has no effect on audit quality through evidence competence, (9) Auditor independence has no effect on audit quality through evidence competence, (10) Auditor professionalism has no effect on audit quality through evidence competence For the R² value shows the contribution of all exogenous variables in explaining the endogenous variables by 88%, the remaining 12% is explained by other variables. For the contribution of all exogenous variables in explaining the intervening variable of 76.7%, the remaining 23.3% is explained by other variables.